ZIS (Zakat, Infaq And Alms) Funds Management Methods In Improving The Quality Of Mustahiq Life In BAZNAS Karanganyar - Darlin Rizki (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: This study aims to analyze the role of philanthropy (ZIS) in reducing poverty and improving the quality of life in the Karanganyar society district.